دراسة تأثير التربيط الفولاذي على تقويم الازاحة للأبنية القائمة المعرضة للهزات الارضية باستخدام التحليل بالسجلات الزمنية الصنعية - نداف, قصي (Latakia University Journal -Engineering Sciences Series, 2019)
The great development in the methods used in structural analysis and the emergence of modern studies that adopt the principle of design transition led us to progress in this research in order to determine the displacement of the structures under the influence of earthquakes using nonlinear dynamic analysis. The frames of the concrete buildings are subject to vertical forces in addition to horizontal forces resulting from wind and earthquakes. Due to the sensitivity of the lateral frames of the lateral transitions, it is useful to improve its behavior to resist the lateral transitions through steel bracing. It is expected that the facilities will be malformed when exposed to severe earthquakes. Therefore, post-flexive behavior should be taken into account when assessing the seismic performance of enterprises. Therefore, it is preferable to use nonlinear analysis procedures for assessment purposes, because behavior beyond flexibility cannot be determined directly through flexible analysis. Furthermore, the seismic seismic demand for the maximal transmission of origin must be determined in order to adequately estimate the expected seismic demand of the origin, which appears in the behavior of the lumen. The objective of this study is to study the effect of steel bracing on the displacement assessment of existing buildings exposed to earthquakes using the synthetic time histories analysis through the case of a study by conducting an applied analytical study on two existing bricklaying models and then using steel bonding in different shapes and locations. Using the time domain and the frequency domain to suit the response spectrum of the Syrian Arab code. The results were discussed after the transfer study. إن التطور الكبير في الطرق المتبعة في التحليل الإنشائي وظهور الدراسات الحديثة التي تعتمد مبدأ الانتقال في التصميم دفعنا إلى التقدم في هذا البحث وذلك بهدف تحديد الانزياح الذي تتعرض له المنشآت تحت تأثير الهزات الأرضية وذلك باستخدام التحليل الديناميكي اللاخطي. تخضع إطارات الأبنية البيتونية لقوى شاقوليه إضافة للقوى الأفقية الناجمة عن الرياح والزلازل. نظرا لحساسية الإطارات البيتونية للانتقالات الجانبية فإنه من المفيد تحسين سلوكها لمقاومة الانتقالات الجانبية وذلك من خلال التربيط الفولاذي. من المتوقع أن تتشوه المنشآت بشكل لا مرن عندما تتعرض لزلازل شديدة، لذلك يجب أن يؤخذ السلوك ما بعد المرن بعين الاعتبار عند تقييم الأداء الزلزالي للمنشآت، وبالتالي يفضل استخدام إجراءات التحليل اللاخطية وذلك لأن السلوك خارج مجال المرونة لا يمكن أن يتحدد مباشرة من خلال التحليل المرن. أكثر من ذلك، يجب أن يتم تحديد الطلب الزلزالي اللامرن للانتقال الأعظمي للمنشأ وذلك للقيام بتقدير كاف للطلب الزلزالي المتوقع للمنشأ والذي يظهر بالسلوك اللامرن. يهدف هذا البحث إلى دراسة تأثير التربيط الفولاذي على تقويم الازاحة للأبنية القائمة المعرضة للهزات الارضية باستخدام التحليل بالسجلات الزمنية الصنعية من خلال حالة دراسة وذلك بإجراء دراسة تحليلية تطبيقية على نموذج فراغي لبناء قائم ومن ثم استخدام التربيط الفولاذي بأشكال ومواضع مختلفة حيث استخدمت سجلات زمنية لزلازل حقيقية تم تقييسها باستخدام طريقتي مجال الزمن ومجال التردد لتلائم طيف الاستجابة للكود العربي السوري، وتمت مناقشة النتائج بعد دراسة الانتقالات.